Dynamic Student’s Public Speaking Through Digital Application - Windy Pramesti, Rahmadini; Arjulayana; Firdaus, Moh Iqbal (Universitas Islam Negeri Palopo, 2025)
This study explores the perceptions of third-semester students in the English Education Study Program at Universitas Muhammadiyah Tangerang regarding the use of the Book Creator application as a digital tool to support the development public speaking especially in application of public speaking elements. Using a descriptive qualitative method, data was collected through interviews with 32 students and 1 lecturer teaching the public speaking course, as well as analysis of student video project documents. The results indicate that 29 out of 32 students experienced improvement in at least one element of public speaking, including facial expressions, eye contact, hand gestures, body movements, and voice. Multimedia features such as video, audio, text, and image insertion encouraged repeated practice, self-evaluation, and increased self-confidence. Students also developed greater creativity and clarity in crafting their messages. These results support the implementation of a reflective and student-centered learning approach in a digital environment. However, this study is limited by its small sample size and single institutional context. Practical implications suggest that educators can integrate Book Creator to develop public speaking skills in a flexible and engaging manner, tailored to the needs and learning styles of learners.